Pengaruh Budaya Organisasi dan Motivasi Intrinsik terhadap Komitmen Afektif dengan Kepuasan Kerja sebagai Variabel Pemediasi pada Karyawan Dinas Koperasi dan UKM Kabupaten Sleman - Erinna Indah Cahyaningrum; Prayekti Prayekti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to examine the effect of organizational culture and intrinsic motivation on affective commitment. This study also aims to examine whether job satisfaction acts as a mediating variable on the influence of organizational culture and intrinsic motivation on affective commitment to the employees of the Cooperatives and SMEs Service Office of Sleman Regency. This study uses the Associative method with a quantitative approach. The population in this study were all employees of the Department of Cooperatives and SMEs in Sleman Regency, with a sample of 45 employees. The sampling technique used saturated sampling with data collection using a questionnaire. The data analysis technique in this study used multiple linear regression, Sobel test, coefficient of determination, and standard beta. This study resulted in the findings that organizational culture has an effect on job satisfaction, and intrinsic motivation has an effect on job satisfaction. Likewise, organizational culture influences affective commitment. However, intrinsic motivation has no effect on affective commitment. Other findings show that job satisfaction has an effect on affective commitment. This study also produces findings that job satisfaction mediates the effect of organizational culture on affective commitment, and job satisfaction also mediates the effect of intrinsic motivation on affective commitment. Keywords: organizational culture, intrinsic motivation, job satisfaction, affective commitment.